Who Pays for Providing Spiritual Care in Healthcare Settings?: the Ethical Dilemma of Taxpayers Funding Holistic Healthcare and the First Amendment Requirement for Separation of Church and State - Warnock, Carla Jean Pease (Journal of religion and health, 2009)
All US governmental, public, and private healthcare facilities and their staff fall under some form of regulatory requirement to provide opportunities for spiritual health assessment and care as a component of holistic healthcare. As often the case with regulations, these facilities face the predicament of funding un-reimbursable care. However, chaplains and nurses who provide most patient spiritual care are paid using funds the facility obtains from patients, private, and public sources. Furthermore, Veteran healthcare services, under the United States Department of Veterans Affairs (VA), are provided with taxpayer funds from local, state, and federal governments. With the recent legal action by the Freedom From Religion Foundation, Inc. (FFRF) against the Veterans Administration, the ethical dilemma surfaces between taxpayers funding holistic healthcare and the first amendment requirement for separation of church and state.